2003
DOI: 10.1016/s0735-1097(02)03009-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy due to sarcomeric gene mutations is characterized by impaired energy metabolism irrespective of the degree of hypertrophy

Abstract: Our data provide evidence of a bioenergetic deficit in genotype-confirmed HCM, which is present to a similar degree in three disease-gene groups. The presence of energetic abnormalities, even in those without hypertrophy, supports a proposed link between altered cardiac energetics and development of the disease phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
267
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(300 citation statements)
references
References 34 publications
24
267
0
9
Order By: Relevance
“…Investigators compared the cardiac phosphocreatine (PCr) to ATP ratio in 31 patients harbouring mutations in the genes for either β-myosin heavy chain, cardiac troponin T, or myosin-binding protein C, and in 24 control individuals. The PCr/ATP ratio was reduced in the patients with HCM by 30% relative to controls, and the reduction was of a similar magnitude in all three disease-gene groups, and not related to the degree or presence of hypertrophy 13,17 . ATP is produced in the mitochondria, but is used elsewhere, mainly by sarcomeric proteins and ion transporters.…”
Section: Energy Depletion Hcm and Diastolementioning
confidence: 76%
See 3 more Smart Citations
“…Investigators compared the cardiac phosphocreatine (PCr) to ATP ratio in 31 patients harbouring mutations in the genes for either β-myosin heavy chain, cardiac troponin T, or myosin-binding protein C, and in 24 control individuals. The PCr/ATP ratio was reduced in the patients with HCM by 30% relative to controls, and the reduction was of a similar magnitude in all three disease-gene groups, and not related to the degree or presence of hypertrophy 13,17 . ATP is produced in the mitochondria, but is used elsewhere, mainly by sarcomeric proteins and ion transporters.…”
Section: Energy Depletion Hcm and Diastolementioning
confidence: 76%
“…Additionally, overall resting myocardial blood flow (assessed using PET and 13 N-labelled ammonia) did not differ between patients with HCM and controls (although the vasodilator 'reserve', assessed using dipyridamole, was blunted) 62 . Accordingly, Crilley et al showed that the myocardial perfusion reserve index in these patients did not correlate with energy impairment 13 . Carriers of the HCM-associated MYBPC3 mutation have reduced myocardial efficiency in the absence of hypertrophy and microvascular dysfunction 63 .…”
Section: [H3] Energy Inefficiency or Ischaemia?mentioning
confidence: 95%
See 2 more Smart Citations
“…Whether impaired energetics in HCM is the consequence, or the cause, of LVH remains unclear. Nonetheless, impaired energy metabolism in HCM exists even in the absence of hypertrophy, suggesting that compromised energetics precede hypertrophy and may play a causal role in the development of the HCM phenotype [28]. Concordantly, HCM cardiomyocytes exhibit sarcomeric mutations resulting in inefficient ATP utilization, with subsequent increased cost of force generation and excess demand on myocytes [29].…”
Section: Myocardial Efficiencymentioning
confidence: 99%